Al-mafahim al-islamiyah fi al-aflam al-malayuwiyah: filem Pendekar Bujang Lapok min ikhraj P.Ramlee namudhzajan = Islamic concepts in Malay film: "Pendekar Bujang Lapok" directed by P. Ramlee as a model - Abdul Razak, Muhammad Anas; Ahmad H.Osman, Rahmah; Mohd Tumiran, Dayang Alwani (Al Hikmah Research and Publication Centre., 2022)
Film is a remarkably effective medium in conveying drama and especially in the evocation of emotion. The film also affects the formation of society’s personality. In this era, there are many films that give negative effects in the life of the community because no Islamic concepts found in that films. The researcher tried to research Islamic concepts present in one of the famous films in Malaysia and their impact on the life of society. This study aims to show the Islamic concepts contained in the movie "Pendekar Bujang Lapok". If these concepts are presented through the axes of the events of the film. So, these questions came about what these concepts are, how they are presented, and the purpose of telling this film that the film director wanted to communicate to the viewer. In addition, this study aims to analyze the effect of this film on the behavior of society. The researcher adopted the descriptive analytical method and used interview and questionnaire as the research tools to get the necessary information and data, in order to achieve the objectives of the study. The results of the research found that this film contains some characteristics of the Islamic civilization found in the land of Malay. In addition, the director also tries to show the human values that existed after the advent of Islam in the land of Malay. The director tries to show the contribution of Islamic civilization in the land of Malay and its impact on the behavior of society.